1999
DOI: 10.1074/jbc.274.16.10852
|View full text |Cite
|
Sign up to set email alerts
|

Unconjugated Bilirubin Exhibits Spontaneous Diffusion through Model Lipid Bilayers and Native Hepatocyte Membranes

Abstract: The liver is responsible for the clearance and metabolism of unconjugated bilirubin, the hydrophobic endproduct of heme catabolism. Although several putative bilirubin transporters have been described, it has been alternatively proposed that bilirubin enters the hepatocyte by passive diffusion through the plasma membrane. In order to elucidate the mechanism of bilirubin uptake, we measured the rate of bilirubin transmembrane diffusion (flip-flop) using stopped-flow fluorescence techniques. Unconjugated bilirub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
100
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 123 publications
(106 citation statements)
references
References 51 publications
5
100
0
1
Order By: Relevance
“…11, right panel). Moreover, addition of BDT, which we previously showed is incapable of spontaneous transmembrane diffusion, 35 did not cause the hyperpolarization phenomenon observed with bilirubin treatment. As bilirubin and BDT exhibit similar inner filter effects, these findings provide further support that the modulation of rhodamine fluorescence is due to bilirubin-specific induction of changes in mitochondrial potential.…”
Section: Effect Of Bilirubin On the Permeability Of Isolated Mitochonmentioning
confidence: 56%
See 4 more Smart Citations
“…11, right panel). Moreover, addition of BDT, which we previously showed is incapable of spontaneous transmembrane diffusion, 35 did not cause the hyperpolarization phenomenon observed with bilirubin treatment. As bilirubin and BDT exhibit similar inner filter effects, these findings provide further support that the modulation of rhodamine fluorescence is due to bilirubin-specific induction of changes in mitochondrial potential.…”
Section: Effect Of Bilirubin On the Permeability Of Isolated Mitochonmentioning
confidence: 56%
“…We 35 and others 79 have shown that unconjugated bilirubin diffuses rapidly through model and native membrane vesicles and that this represents an important mechanism by which bilirubin is taken up into cells. 37 Once inside the cytoplasm, bilirubin likely associates with mitochondrial membranes, as well as other organelles, as a result of high-affinity binding to membrane lipids.…”
Section: Effect Of Bilirubin On the Permeability Of Isolated Mitochonmentioning
confidence: 84%
See 3 more Smart Citations